Age distribution and types of breast lesions among Afghan women diagnosed by fine needle aspiration cytology (FNAC) at a tertiary care centre in Afghanistan: a descriptive cross-sectional study - Ramin Saadaat; Jamshid Abdul-Ghafar; Ahmed Maseh Haidary; Soma Rahmani; Nooria Atta (BMJ Open, 2020)
Objectives In Afghanistan, breast diseases are a common reason for women to visit hospitals. This is the first study in Afghanistan aimed to describe the age distribution and types of breast diseases among patients diagnosed by fine needle aspiration cytology.Design Descriptive cross-sectional study.Setting French Medical Institute for Mothers and Children, Kabul, Afghanistan.Participants The study included 650 patients with breast lesions between 1 April 2015 and 1 April 2019.Results The mean age of diagnosis was 35.38 (SD ±13.11) years, ranging from 15 to 75 years. The most common diagnosis was cancer (24% of all cases). The second most common diagnosed lesion was fibroadenoma, constituting 22.4%, and the third most common lesion was fibrocystic changes, with 15.4% of cases. Inflammatory conditions were diagnosed in 9.7% of cases, granulomatous inflammation in 9.1%, lesions only suspicious for malignancy in 5.5%, lipoma in 2.8% and miscellaneous benign lesions in 11.1%. Cancer was diagnosed at the youngest age of 20 years. Cancer was more common on the left side (62%), and only one case (0.9%) was bilateral.Conclusion Our study showed that cancer was the most commonly diagnosed lesion and was reported at younger ages too. This suggests that physicians should not ignore any breast lump in younger patients and that the possibility of cancer must be considered. Further country-wide studies are suggested to assess breast cancer and associated risk factors.